(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Internet has become everybody’s man Friday these days. Addiction to Internet is a broad term in which compulsive need is there to spend a large amount of time on the internet to an extent that hampers person’s academics, relationships etc. The field of medicine is also not left untouched by this addiction. It becomes essential to assess medical students’ mental dysfunction and also to monitor their academic progress as they are the future doctors of the community.MATERIAL AND METHODS: 582 medical students of Santosh Deemed to be University were selected for this descriptive analytical study by Cochrane’s sample size formula and stratified random sampling. (For Data collection Young’s Internet Addiction Test was applied. The data was analyzed through t -test and Pearson’s correlation coefficient by incorporating SPSS Software (23.0) software.RESULTS: The Current Studies result showed Internet addiction and mental health score mean score for boys and girls was 2.34 ± 0.46 (M), 2.26 ± 0.62 (F) ,2.54 ± 0.31 (M), 2.51 ±0.32 (F) for internet addiction and mental health respectively. There was a positive association of depression and mental health with internet addiction (P - > 0.001). Multiple regression analysis was used to predict possible indicators for addiction towards internet.CONCLUSIONS: Overindulgent use of Internet by the students can lead to anxiety, mood swings and depression and if not restricted can lead to poor academic performance. Monitoring as well as restricting their internet addiction is the need of the hour and that can be achieved through proper counselling sessions.